Democratization of higher education in Angola: inclusion and academic success - Cassinela , Osvaldo Israel Salumbongo; Ckagnazaroff, Ivan Beck (Seven Editora, 2023)
Currently, social inequalities in education are mentioned in numerous studies that concern institutions and governments around the world. However, elite and new middle-class students generally appear to have longer and more successful learning trajectories, unlike students in a disadvantaged economical situation whose learning trajectories are marked by academic failure. This article discusses the social inclusion policies adopted by Angolan higher education institutions in the 2000s, about access to and permanence in higher education, based on the problems encountered at the time. The purpose of this article is to approach aspects related to the democratization of higher education in Angola, discussing some aspects of the fulfillment of the goals of massification and inclusion in education. In this perspective, we approach in particular the affirmative action policies concerning access and permanence, which began in the 2000s and influence the different paths toward the academic (failure) of students. The study is based on a literature review and document analysis. It is concluded that mass access to education is not enough, it is necessary to guarantee permanence in the university, that is, the student must conclude with the expected academic success in the stipulated time. DOI: https://doi.org/10.56238/devopinterscie-010